Prevalence and Factors Associated with Hypertension among Adolescents in Peri-Urban Areas - Oematan, Grouse; Boeky, Daniela L.A.; Limbu, Ribka; Maranatha, Grace; Mege, Stacia (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: Hypertension in adolescents is becoming an increasingly important health issue because it can continue into adulthood and increase the risk of cardiovascular disease later in life. The purpose of this study was to determine the prevalence of hypertension and pre-hypertension and to analyze the related factors in adolescents in peri-urban areas. Methods: This study used a cross-sectional design conducted in October 2023 on 40 Christian Junior High School 4 Mebung students in Alor Regency. The sample selection was purposive, with inclusion criteria of 13–16 years old. Data were collected using structured questionnaires, interviews, and blood pressure measurements. Blood pressure was measured three times to ensure the accuracy of the measurement results. Data analysis included univariate analysis to describe the characteristics of the respondents and chi-square test to assess the relationship between independent variables (sodium intake, physical activity, parental history of hypertension, sleep duration, sleep quality, and stress) with hypertension status. Results: Pre-hypertension prevalence was 30%, and hypertension was 20%. Three factors showed a significant relationship with hypertension: a history of hypertension in the father (p-value = 0.038), high sodium intake (p-value = 0.002), and sleep duration of less than 8 hours (p-value = 0.001). Other factors, such as a history of hypertension in the mother, physical activity, sleep disorders, and stress, did not show a significant relationship. Conclusion: Hypertension in adolescents in peri-urban areas is related to genetic factors and lifestyle behavior. Prevention efforts need to be focused on low-sodium nutritional education, adequate sleep management, and routine blood pressure screening in schools.